(untitled) (Bangladesh Journal of Otorhinolaryngology, 2022)
Background: Neck Space Infections are serious and common diseases that involve several spaces in the neck. Deep neck space infections can be life threatening in diabetic, immunocompromised and elderly patients and special attention should therefore be given to these groups. Objectives: This study was conducted to assess complications of deep neck space infections and its management, etiology, risk factors, presentation, spaces affected and complications among patients admitted in Department of ENT and Head- Neck Surgery in Dhaka Medical College & Hospital. Methods: This was a Cross Sectional Study conducted in the ENT and Head- Neck Surgery Department, Dhaka Medical College & Hospital from January 2016 to June 2016. A total of 150 patients were included who fulfill the selection criteria. Purposive sampling was used to collect data. Statistical analysis was done by SPSS version 21. Results: More than half of the patients (53.30%) came from middle class. Diabetes Mellitus was the most common risk factor (74.5%). Almost all patients presented with neck pain followed by neck swelling, dysphagia, fever and trismus. Organism isolated from drainage fluid was polymicrobial. Streptococcus (51.34%) and staphylococcus (18.60%) were most common organisms isolated. Airway was secured first and then high doses of antibiotics, immediate surgical drainage under local anesthesia were done in 130 (86%) patients. Commonly used antibiotics were ceftriaxone 132(82%), Metronidazole 113(75%) and flucloxacillin 98(65%). Complications were recorded in 55 patients. Most common was airway complication 40(73%). Tracheostomy was done in 17(11.33%) patients. Mortality occurred in 17(11.33%) patients. Conclusion: Early diagnosis and management is essential to prevent complications. Odontogenic infections, poor oral hygiene, lack of nutrition, smoking and tobacco chewing, DM were associated with neck space infection and we can prevent & control those factors. Bangladesh J Otorhinolaryngol 2022; 28(1): 56-61